Speed breeding to accelerate crop improvement - Temesgen Begna (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Global food security has become a major issue as the human population grows and the environment changes, with the current rate of improvement of several important crops inadequate to meet future demand. Crop plants have extended generation times, which contributes to the slow rate of progress. However, speed breeding has revolutionized the entire world by reducing generation time and speeding up breeding and research programs to improve crop varieties. In the absence of an integrated pre-breeding program, breeding new and high-performing cultivars with market-preferred traits can take more than ten years. After the first cross with parental genotypes, a large amount of time, space, and resources are committed to the selection and genetic advancement stages during the early stages of breeding. Speed breeding has the ability to shorten the time it takes to develop, market, and commercialize cultivars. Crop improvement in the face of a fast-changing environment and an ever-increasing human population is a major concern for scientists around the world. Current crop enhancement projects are progressing at a rate that is insufficient to meet food demand. Crop redesign is urgently needed for climate resilience, as well as long-term yield and nutrition. Crop progress is slowed significantly by the long generation time required by crop plants during the breeding process. Speed breeding is now being used on a large scale to shorten generation time and support multiple crop generations per year as a solution in this approach. Researchers are now using an integrated approach to improve breeding efficiency, combining speed breeding with current plant breeding and genetic engineering methods. Speed breeding is a promising approach for achieving nutritional security and sustainable agriculture by shortening breeding cycles for food and industrial crop enhancement. Speed breeding is a methodology that allows plant breeders to improve crop production by adjusting temperature, light duration, and intensity to boost plant development. It uses an artificial source of light, which is kept on continuously, to activate the photosynthetic process, which leads to growth and reproduction much earlier than normal. This will assist in meeting the demands of the future's rising population. This can be accomplished using a variety of technologies, including genotyping, marker-assisted selection, high throughput phenotyping; gene editing, genomic selection, and re-domestication, all of which can be combined with speed breeding to allow plant breeders to keep up with a changing climate and growing human population.